Comparação entre a dose e a distribuição de pontos de aplicação de toxina botulínica tipo A na eficácia para o tratamento de rítides glabelares. Ensaio clínico randomizado duplo cego - Santos, Eduardo Benassi dos (2020)
Botulinum toxin has been used safely and effectively for the treatment of glabellar rhytids. However, clinical practice has been varied, leaving doubts about the optimal dose and the number of injection points. The objective of this work is, therefore, to evaluate the effect of concentration and application points of botulinum toxin in the treatment of glabellar rhytids. Forty volunteers were randomly divided into 4 groups: G1: one injection point in procerus muscle (5U) and one injection point in corrugator muscle (5U); G2: one injection point in procerus muscle (5U) and two injection points in corrugator muscle (2.5U per point); G3: one injection point in procerus muscle (7U) and one injection point corrugator muscle (7U per point); G4: one injection point in procerus muscle (7U) and two injection points in corrugator muscle (5U per point). Participants were assessed at baseline and weeks 2, 8, 10 by the Wrinkle Scale Facial method. The results of this study suggest that at the dosages studied, 21U applied at one point per muscle is an effective dose for the treatment of the glabellar region, lasting 3 months.